THE EFFECT OF COMPANY SIZE, PROFITABILITY, AUDIT COMMITTEE ON AUDIT DELAY WITH PUBLIC ACCOUNTING FIRM SIZE AS MODERATING VARIABLES - Nadira Reskika; Ickhsanto Wahyudi (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This study aims to determine the effect of firm size, profitability, audit committee on audit delay with public accounting firms as moderation in banking companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used was purposive sampling with the number of samples used as many as 25 companies with an observation period of 2018-2020. This research uses multiple linear regression analysis method. Based on the results of the data processing shows that the size of the company is not significant to audit delay. Profitability has no and no significant effect on audit delay. The audit committee is significant to the delay audit. The size of the public accounting firm cannot moderate the effect of firm size on audit delay and is not significant. The size of the public accounting firm cannot moderate the effect of profitability on audit delay and is not significant. The size of the public accounting firm can moderate the effect of the audit committee on audit delay and is significant. Key Word: audit delay, firm size, profitability, audit committee, public accounting firm size